A HYBRID APPROACH IN ACHIEVING ACCURACY AND ROBUSTNESS FOR BIMODAL EMOTION DETECTION THROUGH SPEECH AND FACIAL EXPRESSIONS - KRISHNA , MOHAN KUDIRI (2019)
Improper synchronisation, data correlation, and relationship between human emotions are common issues in emotion detection via facial expressions in speech processing. These issues are more critical in real-world environment due to different intensity of emotions issue, image resolution, random additive noise, and data masking factors. Moreover, emotion detection, through speech and facial expressions by conventional techniques seem to hamper emotion detection accuracy and robustness in the realworld environment.